2022
DOI: 10.17219/dmp/150075
|View full text |Cite
|
Sign up to set email alerts
|

Fear and anxiety of COVID-19 in dental patients during the COVID-19 pandemic: A cross-sectional survey in Turkey

Abstract: The authors thank the study participants for their contribution and especially acknowledge the clinical staff for their assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…A survey conducted in Turkey showed that 73% of participants feared dental treatment because of the possibility of contracting the virus in the dental office. 29 Moreover, the literature reports that the likelihood of treatment discontinuation is 6 times higher in people with a high level of fear of coronavirus and 8 times higher in the elderly. 14 Almost 25% of respondents changed their treatment date during the periods of increased infection rate due to the possibility of infection.…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted in Turkey showed that 73% of participants feared dental treatment because of the possibility of contracting the virus in the dental office. 29 Moreover, the literature reports that the likelihood of treatment discontinuation is 6 times higher in people with a high level of fear of coronavirus and 8 times higher in the elderly. 14 Almost 25% of respondents changed their treatment date during the periods of increased infection rate due to the possibility of infection.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 triggers hypercoagulation and causes neurological damage, and, in severe cases, leads to death. Fever, cough, runny nose, nasal congestion, anosmia, dysgeusia/hypogeusia, diarrhea, and nausea/vomiting are the most typical symptoms [ 24 , 25 ]. Fatigue, eye discomfort (conjunctival discharge), and arrhythmias are other clinical signs.…”
Section: Introductionmentioning
confidence: 99%
“…6 Fear for dental treatment can also be affected or compounded by some situations that can impact on the psychological well-being of the patient such as the COVID-19 pandemic. Studies 8,9 have shown that the pandemic added to the anxiety and fear of visiting the dental clinic, due to the fear of meeting people and increasing their risk of contracting the disease. However, this study plans to focus on a normal situation where there is no external nor additional situation such as the pandemic.…”
Section: Introductionmentioning
confidence: 99%